Development of a portable display system with a human-centered design approach - Landqvist, Fredrik (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
This master thesis project in industrial design engineering at Luleå University of Technology was about developing a portable light box for Spennare. The work was done under the supervision of the design engineering studio Catino in Stockholm during the spring of 2020. The background for the project was that Spennare today has a large selection of display system products that companies can use to promote themselves, such as roll-up screens and pop-up walls. But a product they does not have in their range is a portable lightbox. A portable lightbox differs from roll-ups and similar products in the way that the message that is conveyed becomes backlit, since the lightbox contains LED lights. This differentiates the lightbox amongst other similar products and the message is conveyed in a clearer and more prominent way than with a roll-up which is not backlit. The work has followed a user-centered design process that has followed a framework called Double Diamond developed by the Design Council (Design Council, n.d.). The framework consists of four phases: discover, define, develop and deliver. The purpose of the process was to first create an understanding of what the problem was, and then to concretize it into some well-formulated problems and needs that needed to be solved and fulfilled. Then ideas for solutions to these problems would be generated, ideas that could then be refined and evaluated until final solution were reached. Methods used during the process was benchmarking, interviews, observations and tests to identify the problem. Then, among other things, different brainstorming methods have been used during both creative workshops but also throughout the process of generating ideas. In order to test and evaluate different ideas, prototypes have been built in different stages during the process. The final result was compiled in a cad model. In the initial phase of the processes, when an understanding of the problem was developed, showed that many of the existing lightboxes consist of many different parts ...